BIO-GATS: A Tool for Automated GPCR Template Selection Through a Biophysical Approach for Homology Modeling - Jabeen, Amara; Vijayram, Ramya; Ranganathan, Shoba (Frontiers in Molecular Biosciences, 2021)
G protein-coupled receptors (GPCRs) are the largest family of membrane proteins with more than 800 members. GPCRs are involved in numerous physiological functions within the human body and are the target of more than 30% of the US Food and Drug Administration (FDA) approved drugs. At present, over 400 experimental GPCR structures are available in protein databank (PDB) representing 76 unique receptors. The absence of an experimental structure of the majority GPCRs demand homology models of GPCRs for structure-based drug discovery workflows. The generation of good homology models requires appropriate templates. The commonly used methods for template selection are based on sequence identity. However, there exists a low sequence identity among the GPCRs. The sequences with similar patterns of hydrophobic residues are often structural homologs even sharing low sequence identity. Based on this, we propose a biophysical approach for template selection based principally on hydrophobicity correspondence between the target and the template. Our approach takes into consideration other relevant parameters as well, including resolution, similarity within the orthosteric binding pocket of GPCRs, and structure completeness, for template selection. The proposed method was implemented in the form of a free tool called Bio-GATS, to provide the user with easy selection of the appropriate template for query GPCR sequence. Bio-GATS was successfully validated with recent published benchmarking datasets. An application to an olfactory receptor to select appropriate templates has also been provided as a case study.